Media Technology Creating 'Sermonic Events.' The Hillsong Megachurch Network - Klaver, Miranda (Cross currents, 2015)
The article discusses the modes of preaching practices enhanced by the possibilities of media technology, based on an ethnographic research in global megachurch networks, like Hillsong New York City and Hillsong Amsterdam. Topics covered include the challenges posed by the network to the characteristics of live preaching in terms of coherence between time and place, embodiment and performance, and the transformation of the sermon into a sermonic event.